Selection of Hormonal Reference Values for Undescended Testicle Case in 8-Year-Old Boy with Abnormal Chromosome - Vina Corry; Merci M. Pasaribu (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Establishing the diagnosis of undescended testicles requires appropriate hormonal laboratory reference values based on age and gender. An 8-year-old boy with an undescended testicle, mental retardation, and stunting had a blood test that was carried out at the Clinical Pathology Laboratory, dr. Cipto Mangunkusumo (RSCM) Hospital on February 6, 2020, with testosterone levels of 0.69 nmol/L (N male: 4.94-32.01 nmol/L) indicating decreased testosterone levels. The patient was consulted from urological surgery to pediatric endocrinology to determine the presence or rudiment of the patient'stesticles. Using the reference range of testosterone values assists clinicians in determining the diagnosis, monitoring therapy, and prognosis of a disease. There are some testosterone reference values, which are currently available, including Canadian Laboratory Initiative on Pediatric Reference Intervals Database (CALIPER) and the Tanner stage reference value. Later is more applicable because it is based on chronological age and secondary sexual development in assessing puberty development. A case of an 8-year-old boy with a clinical diagnosis of an undescended testicle, the laboratory test resultsshowed normal-low testosterone levels using the CALIPER and Tanner stage ranges according to the patient's age. No increase of testosterone levels after the second HCG stimulation test might be due to differences in the HCG administration protocol; therefore, the diagnosis of anorchia had not been established, and chromosome abnormalities of 46 XY, +6 Mar, 17 dmin on chromosome analysis suggested the suspected syndrome. These findings were consistent with the suspicion of primary hypogonadism in children with suspected syndrome caused by bilateral cryptorchidism with a suspected seminiferous tubular defect.